methods and case studies - Campbell, Nicole (Chicago, Ill., 2001)
This book inclubes: chapter 1 defines the concept of usability and provides a synopsis of methods for measuring usability. Chapter 2 discusses some of the important elements to consider when conducting a usability study.
Keywords: Library Web sites,Library Web sites,Library information networks,Web site development; Use studies,Design